<span> here
7 7/8
= [ (8*7) + 7 ] / 8
= (56 + 7) / 8
=63 / 8
similarly,
3 1/4
=[ (4*3) + 1] / 4
= (12 + 1) / 4
= 13/4
----------------------------
now put the values
7 7/8 - 3 1/4
= 63/8 - 13/4
here, take LCM of 8 & 4 which is 8.
now,
[ (1*63) - (2 * 13) ] / 8
= (63 - 26) / 8
= 37/8
= 4 5/8........................[ here, divide 37 by 8 which gives reminder as 5 and divisible value as 4 ]</span>
Answer:
26V + 2
Step-by-step explanation:
This is the same as saying f(g(x)), where x = 26
First, lets figure out what g(x) is equal to when x = 26
g(26) = V(26) - 1 = 26V - 1
Now we input 26V - 1 into f(x) for x
f(26V-1) = (26V-1) + 3 = 26V + 2
Answer:
18
Step-by-step explanation:
18
2 * 9 = 18
9 + 9 = 18
Answer:
6
Step-by-step explanation:
first, set up the equation
4x+7 = x+25
solve for x:
4x = x + 18
3x = 18
x = 6
have a wonderful day! :)
Answer:
Wat is the question?
Step-by-step explanation: